2010
DOI: 10.1159/000321194
|View full text |Cite
|
Sign up to set email alerts
|

Induction of B Cell-Activating Factor by Viral Infection Is a General Phenomenon, but the Types of Viruses and Mechanisms Depend on Cell Type

Abstract: B cell-activating factor of the TNF family (BAFF) plays a key role in promoting B lymphocyte activation and survival. We previously showed in primary Sjögren’s syndrome that salivary gland epithelial cells (SGECs), the resident targeted cells of autoimmunity in this disease, can produce BAFF after infection with a double-stranded RNA (dsRNA) virus by a protein kinase RNA (PKR)-dependent mechanism. This study aimed to assess the effect of different viruses on various cell types – SGECs but also dendritic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
4
26
0
1
Order By: Relevance
“…1A, BAFF mRNA levels were not increased in MDMs early postinfection (i.e., 24 to 72 h) with fully infectious R5-tropic NL4-3Balenv viruses compared with uninfected control cells. The TLR3 agonist poly(I:C) and IFN-a were used as positive controls in the current studies due to their known capacity to upregulate BAFF expression in different cell types, including macrophages (25,30,49,50). Next, we assessed BAFF secretion in MDM supernatants at similar time points using a commercial ELISA kit.…”
Section: Hiv-1 Increases Baff Expression and Secretion In Mdmsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A, BAFF mRNA levels were not increased in MDMs early postinfection (i.e., 24 to 72 h) with fully infectious R5-tropic NL4-3Balenv viruses compared with uninfected control cells. The TLR3 agonist poly(I:C) and IFN-a were used as positive controls in the current studies due to their known capacity to upregulate BAFF expression in different cell types, including macrophages (25,30,49,50). Next, we assessed BAFF secretion in MDM supernatants at similar time points using a commercial ELISA kit.…”
Section: Hiv-1 Increases Baff Expression and Secretion In Mdmsmentioning
confidence: 99%
“…BAFF belongs to the TNF superfamily and acts as a potent regulator of B cell development and functions, including peripheral B cell survival, maturation, Ig production and CD40-independent Ig class-switch recombination (22)(23)(24). BAFF protein is mainly expressed by myeloid cells, such as monocytes, macrophages, and dendritic cells, but also by nonmyeloid cell types and epithelial cells (22,23,25). BAFF is an essential component of B cell homeostasis, but excess production, as observed in several autoimmune diseases and chronic infections, results in B cell hyperplasia, lymphoproliferation, hypergammaglobulinemia, and symptoms of autoimmunity (26,27).…”
mentioning
confidence: 99%
“…BAFF exists as membrane-bound protein and in a soluble form (27), which has been shown to aggregate into 3-mers or 60-mers depending on the primary structure of the protein (27)(28)(29)(30)(31)(32)(33). The cytokine is produced by hematopoietic (23) as well as by nonhematopoietic cells (34), and its expression has been found to be upregulated by proinflammatory responses (23,27,34,35), during viral infections (25,36,37), and in various autoimmune conditions (8,10,(38)(39)(40).…”
Section: Baff Concentrations In Patients With Padmentioning
confidence: 99%
“…have shown also that increased BAFF levels observed in certain chronic autoimmune disorders and chronic inflammatory diseases were associated to an elevated type I IFN response (48)(49)(50). Moreover, in vitro studies have demonstrated that viruses can induce high expression of BAFF through a type I IFN pathway in different cell types (43,44). Therefore, we evaluated the possible involvement of type I IFN in the virus-directed BAFF production by human monocytes.…”
Section: Hiv-1-induced Baff Secretion In Monocytes Relies On Type I Imentioning
confidence: 97%
“…1A, BAFF mRNA levels were increased upon exposure to both NL4-3 and NL4-3Balenv (called Bal hereinafter) compared with controls (called mock hereinafter). The TLR3 agonist poly(I:C) was used as a positive control in the current studies due to its known capacity to upregulate BAFF expression in different cell types (43)(44)(45). BAFF, as other members of the TNF superfamily, can be produced as a soluble protein (23).…”
Section: Hiv-1 Increases Baff Expression and Secretion In Human Monocmentioning
confidence: 99%